Digital Financial Inclusion and Its Societal Impact in Emerging ‎Economies - Vidhya , P.; Shetty, Sharan Kumar; Popescu, Virgil; Birau, Ramona; Devaram , N.; Devaki , M.; Margaritescu, Stefan; (Filip), Gabriela Ana Maria Lupu; Renukadevi, D.; Manochithra, P. (International Journal of Accounting and Economics Studies, 2025)
Digital financial inclusion (DFI) has become a pivotal driver of economic transformation in emerging economies, providing previously ‎underserved populations with unprecedented access to financial services. This study examines the societal impact of DFI, with a particular ‎emphasis on its contributions to economic empowerment, improved access to credit, and enhanced financial literacy. Employing a mixed-methods approach, the research integrates both quantitative and qualitative analyses to capture the experiences and perspectives of 450 respondents from diverse socio-economic backgrounds. The study utilizes two complementary analytical techniques: statistical modeling and ‎thematic analysis. Statistical methods are applied to survey data to identify correlations between the use of digital financial services (DFS) ‎and key indicators, including income stability, financial security, and access to economic resources. Concurrently, a thematic analysis of in-depth interviews provides insight into the subtler societal effects of DFI, such as changes in financial behavior, decision-making patterns, and attitudes toward money management. Findings reveal that DFI substantially enhances financial inclusion, particularly for women and ‎rural communities, by offering affordable and accessible avenues for financial participation. Nonetheless, persistent challenges—such as ‎limited digital literacy, inadequate infrastructure, and low trust in digital platforms—continue to constrain its full potential. The study concludes with policy recommendations designed to address these barriers, thereby maximizing the societal benefits of digital financial inclusion in emerging economies.
Keywords: Digital Finance; Financial Inclusion; Emerging Economies; Socio-Economic Impact; FinTech; Poverty Reduction